Demystifying the Discussion of Sequencing Panel Size in Oncology Genetic Testing - Cecília Durães; Carla Pereira Gomes; Jose Luis Costa; Luca Quagliata (European Medical Journal)
Clinical laboratories worldwide are implementing next-generation sequencing (NGS) to identify cancer genomic variants and ultimately improve patient outcomes. The ability to massively sequence the entire genome or exome of tumour cells has been critical to elucidating many complex biological questions. However, the depth of information obtained by these methods is strenuous to process in the clinical setting, making them currently unfeasible for broader adoption. Instead, targeted sequencing, usually on a selection of clinically relevant genes, represents the predominant approach that best balances accurate identification of genomic variants with high sensitivity and a good cost-effectiveness ratio. The information obtained from targeted sequencing can support diagnostic classification, guide therapeutic decisions, and provide prognostic insights. The use of targeted gene panels expedites sample processing, including data analysis, results interpretation, and medical reports generation, directly affecting patient management. The key decision factors for selecting sequencing methods and panel size in routine testing should include diagnostic yield and clinical utility, sample availability, and processing turnaround time. Profiling by default all patients with late-stage cancer with large panels is not affordable for most healthcare systems and does not provide substantial clinical benefit at present. Balancing between understanding cancer biology, including patients in clinical trials, maximising testing, and ensuring a sustainable financial burden for society requires thorough consideration. This review provides an overview of the advantages and drawbacks of different sizes NGS panels for tumour molecular profiling and their clinical applicability.